2011
DOI: 10.2486/indhealth.ms1230
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanical Effect of Anterior Pelvic Tilt Taping on Slump Sitting by Seated Workers

Abstract: The objectives of this study were to determine whether there is a change in the pelvic inclination after about 30 min of slump sitting by seated workers, and if so, to determine whether these changes can be prevented by the application of anterior pelvic tilt taping (APTT). The subjects who consented to participate in the experiment were randomly allocated to two groups: no-APTT group and APTT group. The no-APTT group performed slump sitting for 30 min, and the both pelvic inclinations were remeasured. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 33 publications
0
16
0
1
Order By: Relevance
“…Han et al13 ) reported a mechanical effect of using a kinesiology tape on a rounded shoulder posture. Lee et al14 ) demonstrated that a change in the pelvic angle can be caused by applying the Anterior Pelvic Tilt Taping (APTT), a mechanical method, to the slump sitting of the workers who work sitting for a long time. Another mechanism can be described as a methodological part of the AET.…”
Section: Discussionmentioning
confidence: 99%
“…Han et al13 ) reported a mechanical effect of using a kinesiology tape on a rounded shoulder posture. Lee et al14 ) demonstrated that a change in the pelvic angle can be caused by applying the Anterior Pelvic Tilt Taping (APTT), a mechanical method, to the slump sitting of the workers who work sitting for a long time. Another mechanism can be described as a methodological part of the AET.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown the effects of kinesiology taping on pain control10, 11 ) , joint support12, 13 ) , and muscle function14, 15 ) . Therefore, the aim of this study was to determine whether kinesiology taping decreases the repositioning error of the knee joint after quadriceps fatigue and ultimately confirm if kinesiology taping can improve joint position sense.…”
Section: Introductionmentioning
confidence: 99%
“…Contribuindo, Karatas et al 28 citam que o efeito fisiológico da bandagem é normalmente visto 72 horas após a aplicação. Entretanto, em um estudo de Lee e Yoo 29 que utilizou a bandagem funcional para buscar a inclinação anterior da pelve, foi verificado efeito imediato após, ocorrido apenas com 30 minutos de intervenção, corroborando com os achados encontrados no presente estudo. Porém, houve pouca alteração nos achados no período do pré-imediato ao pós-72h.…”
Section: Discussionunclassified